Work-Life Balance of Married Female Teachers During Pandemic in the Philippines: A Qualitative Metaphorical Analysis - Delavin, Elreen Aguilar; Pogoy, Angeline M. (Future Science / FSH-PH Publications, 2023)
Work-life balance is a cycle of one's life experiences which means satisfaction with work, family, and self. The study explored the self-representation of married female teachers with their work-life balance in Philippine public schools during pandemics through qualitative research using metaphorical analysis. The participants' metaphors of their work-life balance were identified in the interview, such as being like a drained cellphone, melting candle, strong and big tree, spider, COVID-19 vaccine, and season. Also, several studies revealed that they juggle multiple roles during pre-pandemic. Hence, their experiences in terms of work-life balance have advantages and disadvantages during the pandemic, which may worsen or lighten the current roles they have. Thus, it is recommended to raise more awareness of women's work-life balance in their organizations or agencies. Also, strengthening Republic Act 9710 in the workplace is highly recommended.